Analisis Teoretis Desain Alat Pemanas Tenaga Surya dalam Menunjang Efisiensi Pengeringan Gabah - Cipta, Abiel Mulya (Journal of Science and Technology: Alpha, 2025)
Rice drying is a pivotal post-harvest operation that directly influences grain quality, storability, and market value. Conventional sun drying methods, while widely practiced, are highly dependent on weather conditions and often result in inconsistent moisture reduction. In response to these limitations, solar-powered heating systems offer a sustainable and environmentally friendly alternative for controlled drying processes. This study presents a theoretical analysis of various solar heater design configurations and their potential impact on the efficiency of rice drying. The research adopts a literature-based approach, synthesizing findings from previous studies on solar collector geometry, heat absorber materials, insulation techniques, and airflow mechanisms. Thermodynamic principles, including heat transfer via conduction, convection, and radiation, serve as the analytical framework to evaluate the performance of different design models. Key parameters such as collector tilt angle, surface absorptivity, glazing properties, and thermal insulation are examined for their influence on drying temperature, humidity control, and drying rate. Findings indicate that optimal collector orientation, selective coating on absorber plates, and effective insulation significantly enhance thermal efficiency. Additionally, airflow systems—whether passive or active—play a crucial role in maintaining uniform temperature distribution and reducing relative humidity within the drying chamber. Simulated thermal models and empirical data from referenced studies suggest that solar-powered dryers can achieve moisture reduction levels that meet national standards for milled rice, with minimal energy input and reduced environmental impact. This theoretical investigation provides a conceptual foundation for the development of solar-based rice drying technologies tailored to tropical climates. It highlights the importance of integrated design strategies that combine thermal performance, material selection, and ergonomic considerations. The study aims to support future innovations in post-harvest processing and contribute to energy-efficient agricultural practices in rural communities.